2018
DOI: 10.3390/ijerph15050947
|View full text |Cite
|
Sign up to set email alerts
|

Use of Diabetes Treatment Satisfaction Questionnaire in Diabetes Care: Importance of Patient-Reported Outcomes

Abstract: The efficacy of diabetes treatment should not be evaluated solely by HbA1c levels as they should also focus on patient-reported outcomes (PROs), such as patient satisfaction, wellbeing and quality of life. The Diabetes Treatment Satisfaction Questionnaire (DTSQ) has been developed to assess patient satisfaction with diabetes treatment. DTSQ has been translated into more than 100 languages and is widely used in many countries, since it is relatively easy to answer and is used for both patients with and without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 19 publications
1
86
0
2
Order By: Relevance
“…31 The DTSQ was used as it is a validated tool for measuring treatment satisfaction in patients with diabetes. 13 In SUSTAIN 7, an open-label trial 24 in which patients administered treatment with a multi-use pen device without a hidden needle for semaglutide or a single-use pen with a hidden needle for dulaglutide, changes in overall treatment satisfaction were similar for both treatments. Previous studies have shown a preference for the dulaglutide device when compared with devices similar to that used with semaglutide.…”
Section: Discussionmentioning
confidence: 98%
“…31 The DTSQ was used as it is a validated tool for measuring treatment satisfaction in patients with diabetes. 13 In SUSTAIN 7, an open-label trial 24 in which patients administered treatment with a multi-use pen device without a hidden needle for semaglutide or a single-use pen with a hidden needle for dulaglutide, changes in overall treatment satisfaction were similar for both treatments. Previous studies have shown a preference for the dulaglutide device when compared with devices similar to that used with semaglutide.…”
Section: Discussionmentioning
confidence: 98%
“…There is limited evidence of improvement in treatment satisfaction being associated with improved feelings of self-efficacy and better treatment adherence [20]. Certainly, there appears to be a link between higher treatment satisfaction and lower treatment dropout [20]. While the 24-week follow-up in OPTIMIZE is short for assessing treatment compliance, a low level of dropout was observed in this study (one discontinuation and one for minor protocol deviations).…”
Section: Discussionmentioning
confidence: 60%
“…Given the lower blood glucose peak postbreakfast with Gla-300 OD at 6 months versus baseline, there was a smaller drop in blood glucose levels post-breakfast to pre-lunch, which may have contributed to the hyperglycaemia perception DTSQs scores. There is limited evidence of improvement in treatment satisfaction being associated with improved feelings of self-efficacy and better treatment adherence [20]. Certainly, there appears to be a link between higher treatment satisfaction and lower treatment dropout [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many benefits associated with increased patient satisfaction levels, including but not limited to: increased compliance to medication, improved interpersonal relations and productivity, increased patient loyalty, enhanced market share of hospitals, and decreased malpractice claims [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%